The Anticancer Properties of Tanshinones and the Pharmacological Effects of Their Active Ingredients - Fu, Li; Han, Bing; Zhou, Yang; Ren, Jie; Cao, Wenzhi; Patel, Gopal; Kai, Guoyin; Zhang, Jun (Frontiers in Pharmacology, 2020)
Cancer is a common malignant disease worldwide with an increasing mortality in recent years. Salvia miltiorrhiza, a well-known traditional Chinese medicine, has been used for the treatment of cardiovascular and cerebrovascular diseases form thousands of years. The liposoluble tanshinones in S. miltiorrhiza are important bioactive components and mainly include tanshinone IIA, dihydrodanshinone, tanshinone I and cryptotanshinone. Previous studies showed that these four tanshinones exhibited distinct inhibitory effects on tumor cells through different molecular mechanisms in vitro and in vivo. The mechanisms mainly include the inhibition of tumor cell growth, metastasis, invasion, angiogenesis, apoptosis induction, cell autophagy, and anti-tumor immunity and so on. In this review, we described the latest progress on the anti-tumor functions and mechanisms of these four tanshinones to provide a deeper understanding of the efficacy. In addition, the important role of tumor immunology is also reviewed.